2008
DOI: 10.1038/cdd.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

TCTP protects from apoptotic cell death by antagonizing bax function

Abstract: Translationally controlled tumor protein (TCTP) is a potential target for cancer therapy. It functions as a growth regulating protein implicated in the TSC1-TSC2 -mTOR pathway or a guanine nucleotide dissociation inhibitor for the elongation factors EF1A and EF1Bb. Accumulating evidence indicates that TCTP also functions as an antiapoptotic protein, through a hitherto unknown mechanism. In keeping with this, we show here that loss of tctp expression in mice leads to increased spontaneous apoptosis during embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
196
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(211 citation statements)
references
References 39 publications
14
196
1
Order By: Relevance
“…The three-dimensional structures of the following TCTP proteins were solved and are deposited in the databases: The solution structures of fission yeast (Thaw et al 2001) and human TCTP (Feng et al 2007a), as well as the crystal structures of Plasmodium knowlesi (Vedadi et al 2007) and human TCTP (Susini et al 2008) at 2 Å resolution. A mutant version of human TCTP showing a structure very similar to the normal protein (Dong et al 2009) can be found as well.…”
Section: Molecular Structure Conservation and Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The three-dimensional structures of the following TCTP proteins were solved and are deposited in the databases: The solution structures of fission yeast (Thaw et al 2001) and human TCTP (Feng et al 2007a), as well as the crystal structures of Plasmodium knowlesi (Vedadi et al 2007) and human TCTP (Susini et al 2008) at 2 Å resolution. A mutant version of human TCTP showing a structure very similar to the normal protein (Dong et al 2009) can be found as well.…”
Section: Molecular Structure Conservation and Interactionsmentioning
confidence: 99%
“…Since then, the anti-apoptotic activity of TCTP has been reported on numerous occasions and in a range of different settings, which will be discussed below. Major support for the cytoprotective role of TCTP came from gene-knockout studies in mice, which demonstrated that TCTP-knockout was embryonic lethal, due to excessive apoptosis at an early embryonic state (Susini et al 2008;Chen et al 2007a;Koide et al 2009). The following mechanisms have been proposed to underlie the anti-apoptotic activity of TCTP/fortilin: …”
Section: Anti-apoptotic Activity: Discovery and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…TCTP is a growth-regulating protein implicated in the TSC1-TSC2-mTOR pathway 21 and protects cells from apoptotic cell death by antagonizing bax function. 22,23 In addition, TCTP has been suggested as a predictive marker for colon adenocarcinoma progression and tumor metastasis. 24 The increased expression of TCTP in FTC versus FA was confirmed by Western blot analysis (Figure 4).…”
Section: Differential Protein Expression In Fa and Ftcmentioning
confidence: 99%